2021
DOI: 10.7326/m20-7547
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response After SARS-CoV-2 Infection and Implications for Immunity

Abstract: Antibody tests for SARS-CoV-2, the virus that causes COVID-19, are widely available. This living review summarizes the evidence on the prevalence, levels, and durability of detectable antibodies after SARS-CoV-2 infection and whether antibodies to SARS-CoV-2 confer protective immunity. The review will be updated as more evidence becomes available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(86 citation statements)
references
References 76 publications
5
74
0
1
Order By: Relevance
“…It is well known that antibody levels correlate with protection against many viruses including SARS-CoV-2, and recent data suggest that high neutralizing titers are particularly important for protection against the novel SARS-CoV-2 causing the COVID-19 pandemic. 12,13 In the current study we used the Euroimmune ELISA assay to quantify SARS-CoV-2 antibody level as it was reported to highly correlate with the neutralizing antibody assay. 14 Our findings demonstrated that untreated COVID-19-vaccinated MS patients developed protective SARS-CoV-2 humoral responses similarly to healthy vaccinees, and similarly to the findings recently reported in the literature for non-MS vaccinees.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that antibody levels correlate with protection against many viruses including SARS-CoV-2, and recent data suggest that high neutralizing titers are particularly important for protection against the novel SARS-CoV-2 causing the COVID-19 pandemic. 12,13 In the current study we used the Euroimmune ELISA assay to quantify SARS-CoV-2 antibody level as it was reported to highly correlate with the neutralizing antibody assay. 14 Our findings demonstrated that untreated COVID-19-vaccinated MS patients developed protective SARS-CoV-2 humoral responses similarly to healthy vaccinees, and similarly to the findings recently reported in the literature for non-MS vaccinees.…”
Section: Discussionmentioning
confidence: 99%
“…Our evaluation of serological responses is one of few in the community to our knowledge and highlights that a significant minority (~20%) of RT-PCR-positive cases do not appear to seroconvert, particularly those with higher Ct values and not reporting symptoms. A recent systematic review estimated that 95% of adults with laboratory confirmed SARS-CoV-2 infection developed IgG antibodies ( Arkhipova-Jenkins et al, 2021 ), peaking around 25 days. However, only 23% of included studies were in outpatient settings and 14% included only participants with asymptomatic or mild disease.…”
Section: Discussionmentioning
confidence: 99%
“…The first class to be activated through the entry of an infectious agent are immunoglobulins IgM, followed by IgA and IgG. 23 Dimeric IgA can be found on mucosal surfaces and in secretions, such as saliva, breast milk and nasal mucus. Hence, IgA also plays a crucial role for mucosal immunity.…”
Section: Persistence Of Humoral Responsementioning
confidence: 99%
“…In general, it should be noted that test procedures including test timing, assay types, targeted antibodies/antigens and positivity thresholds varied considerably across reviewed studies, as no standard procedures have yet been established. 23 Several immunoassays have not been approved by health and safety agencies such as the US Food and Drug Administration 2 , 23 and numerous studies reviewed here developed their own in‐house tests. More in depth details such as diagnostic test accuracy and approvals for the most common tests have been summarized by previous more rigorous reviews.…”
Section: Persistence Of Humoral Responsementioning
confidence: 99%